2023
DOI: 10.1080/09644016.2022.2156174
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Environmental Peace and Conflict Research

Abstract: Interest in the intersections of environmental issues, peace and conflict has surged in recent years. Research on the topic has developed along separate research streams, which broadened the knowledge base considerably, but hardly interact across disciplinary, methodological, epistemological and ontological silos. Our forum addresses this gap by bringing into conversation six research streams on the environment, peace and conflict: environmental change and human security, climate change and armed conflict, env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…The contributions connect these debates by employing diverse sets of theories (Ide et al, 2023). Political ecology perspectives are particularly prominent in this special issue.…”
Section: From Climate Conflict To Environmental Peacebuildingmentioning
confidence: 99%
See 1 more Smart Citation
“…The contributions connect these debates by employing diverse sets of theories (Ide et al, 2023). Political ecology perspectives are particularly prominent in this special issue.…”
Section: From Climate Conflict To Environmental Peacebuildingmentioning
confidence: 99%
“…In this introduction and the wider special issue, we advocate dialogue between these streams (Ide et al, 2023). We first combine the two research fields that have hitherto often been treated separately by connecting climate-conflict research to environmental peacebuilding.…”
Section: Introductionmentioning
confidence: 99%
“…• Ecological economics moves beyond the dominant orthodoxy to envision an economy that serves the common good and fulfills essential needs, while respecting planetary boundaries (Herman and Cobb, 1994;Raworth, 2017). • Research on various forms of conflict resolution, such as the diverse field of environmental peace and conflict research, provides insights in the multiple ways peace in human societies is connected to the health of their environment (Ide et al, 2023). • In the social sciences more broadly, the field of transformative research proposes a methodology for research to contribute to the elimination of exploitation based on ethnic, gender, or age-group; formulating research questions and conducting the research in partnership with the researched communities (Mertens, 2008).…”
Section: Progress As Regenerationmentioning
confidence: 99%
“…The work of the UN Security Council has been an important line of enquiry (Scartozzi, 2022;Conca, 2018;Zhou, 2017) reflecting a gap in understanding of the role of peace and security actors in the climate emergency. In considering the ''Future of Environmental Peace and Conflict Research,' 'Ide et al (2023) highlight the diverse contributions of six fields: environmental change and human security, climate change and conflict, environmental peacebuilding, political ecology, decolonizing of the environment, and of environmental security. Overall, it is found that climate security just like environmental peacebuilding has struggled to meaningfully engage on gender (Ide et al, 2021a(Ide et al, , 2021bSIPRI, 2022) and on climate finance (UNDP, 2021; Wong, 2022b).…”
Section: Climate Security Environmental Peacebuilding and Gendermentioning
confidence: 99%
“…The climate security field (Adger et al, 2014; Buhaug & von Uexkull, 2021; Burke et al, 2015; Busby, 2018; Dabelko et al, 2013; Hendrix, 2018; Ide et al, 2023; Lee, 2020) offers a much-needed perspective on the intersection between climate change and drivers of conflict and fragility, essentially a “dual burden” of climate and fragility (Busby et al, 2018; Smith & Vivekananda, 2007) showing how climate change can exacerbate underlying drivers of conflict and insecurity. It is a perspective that has otherwise been little acknowledged until recently in mainstream literature or practice in climate change policy or finance.…”
Section: Climate Security Climate Finance and Peacebuilding Finance L...mentioning
confidence: 99%